4a-7=7

To remove the radical on the left side of the equation, square both sides of the equation.

4a-72=72

Multiply the exponents in ((4a-7)12)2.

Apply the power rule and multiply exponents, (am)n=amn.

(4a-7)12⋅2=72

Cancel the common factor of 2.

Cancel the common factor.

(4a-7)12⋅2=72

Rewrite the expression.

(4a-7)1=72

(4a-7)1=72

(4a-7)1=72

Simplify.

4a-7=72

Raise 7 to the power of 2.

4a-7=49

4a-7=49

Move all terms not containing a to the right side of the equation.

Add 7 to both sides of the equation.

4a=49+7

Add 49 and 7.

4a=56

4a=56

Divide each term by 4 and simplify.

Divide each term in 4a=56 by 4.

4a4=564

Cancel the common factor of 4.

Cancel the common factor.

4a4=564

Divide a by 1.

a=564

a=564

Divide 56 by 4.

a=14

a=14

a=14

Solve for a square root of 4a-7=7